The Influence of Service Quality, Religious Commitment and Trust on The Customers’ Satisfaction and Loyalty and Decision to Do The Transaction in Mandiri Sharia Bank Of Jawatimur - Rachmad Hidayat; Sabarudin Akhmad (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This study tested the causal relationship of service quality, religious commitment and trust on customers’ satisfaction, loyalty and decision to repeat their transaction in sharia banking services. This research used quantitative approach to describe the causal relationship between the variables through hypothesis testing. The samples in this research are 160 respondents. Structural equation modeling (SEM) is used to analyze this research. This research findings shows that the quality of service and customers’ trust, satisfaction and loyalty simultaneously influenced the decision to repeat their transaction in that banking service. The customers’ satisfaction and loyalty are intervening variables that linked the service quality and the customers’ trust with the decision to repeat their banking transaction. The religious commitment had insignificant influence toward the service quality; however, it had significant influence toward the loyalty and decision to repeat their banking transaction.